Das Wiener Klavier bis 1850 Bericht des Symposiums "Das Wiener Klavier bis 1850" veranstaltet von der Sammlung alter Musikinstrumente des Kunsthistorischen Museums Wien - Darmstädter, Beatrix (Musikantiquariat und Verlag Hans Schneider, 2008)
The presented book, the amplified proceedings of the symposium "Das Wiener Klavier 1850", held at Neue Burg (Vienna) in 2003 combines as regards content recent organological and biographical research, answers questions concerning the original-instrument performance of the romantic period and focuses on technological features in the making of the Viennese pianoforte. In the 2nd half of the 18th century Vienna became the European centre of production of pianofortes whereas the typical Viennese pianoforte-sound, evolved from special technological and constructional parameters, acted as a stimulant on composers and interprets. Many instrument makers - some of them originally German - working and living in Vienna contributed to this uplifting evolution with their innovative work for the Austrian Court or simply as civic craftsmen. A quite impressive amount of material about their biographies and contracts was investigated and is an integral part of the publication. With the beginning of the 19th century firms in Paris and London were of utmost importance for the pianoforte industry. Broadwood and Erard for instance in an international terrain and started an early mass-production of instruments based on the English action. Beside these instruments the Viennese pianoforte with its German action could not easily compete with. The book contains the analysis of the manufacturing techniques of the Viennese pianoforte and of the company organisations respectively the corporate structures of the comparatively small businessmen in the Austrian region and the Hapsburg Crown lands particularly with regard to the interactions between the Viennese, German and Italian workshops. Moreover the variants in aesthetic design and development of the Viennese pianofortes until the time by 1850 are pointed out and results of recent dendrochronological research of instruments preserved by renowned collections are published in this book.